Pendampingan Budaya Baca melalui Reading Day di TPQ Riyadhusolihin Desa Cibungur - Djachrab, Ida Rapida; Alifianinditta, Putri; Kamilia, Karin (Ma'soem University, 2022)
This research is motivated by the low reading interest of the people in Sumedang Regency. The aim is to foster and socialize a reading culture in elementary school age children. The research subjects were elementary school age students at TPQ Riyadhusolihin, Cibungur Village, Rancakalong District, Sumedang Regency. The method used uses PAR (Participacy Action Research). The findings of the activity are: 1) Students are not used to having time to read; 2) Reading activities are carried out in class related to the subject being taught, 3) Reading is carried out because there is an assignment; 4) TPQ Riyadhusolihin does not yet have reading books outside of textbooks. Recommendations: 1) Make reading activities a culture without being linked to lesson assignments; 2) Reading can be done not only in class but also outside of class in a pleasant atmosphere; 3) TPQ Riyadhusolihin provides light story books related to faith and morality; 4) The government pays special attention through mobile libraries to remote areas that are difficult to reach by transportation.